Local deformation behaviour of saturated silica sand during undrained cyclic torsional shear tests using image analysis. Issue 7 (21st June 2019) - Zhao, Chuang; Koseki, Junichi; Liu, Weichen
Abstract : A series of undrained cyclic torsional shear tests was conducted to investigate the development of local deformations of silica sand specimens directly using an image-based technique and a transparent membrane. The results for saturated sand specimens with varying densities showed that the vertical slippage of sand particles relative to the membrane was initiated at the liquefaction stage. Additionally, the quantity of vertical slippage of dense specimens was lower than that of loose specimens tested under the same conditions. Moreover, measured on the surface of the specimen, the large accumulated movement during cyclic shearing significantly increased the potential for inducing vertical slippage. A comparison of local deformation among the different tests revealed that the threshold of shear strain to generate non-uniform local deformations decreased with an increase in the relative density of the specimen. A lower liquefaction resistance layer, which formed at the upper part of the specimen after initial liquefaction, would accelerate the concentration of local shear strain; this was especially distinct when the specimen was completely liquefied.